AB0145 Tlr4 signaling pathway mediates the senescence of bone marrow- mesenchymal stem cells from systemic lupus erythematosus patients. (15th June 2017) - Ji, J; Wu, Y; Kong, X; Zhang, Z; Gu, Z
Abstract : Background: Previous studies of our research group revealed the senescence of bone marrow-mesenchymal stem cells from systemic lupus erythematosus patients, which participated in the development of SLE. "Inflammatory microenvironment" played a very important role in cellular senescence. In the preliminary experiments, we discovered the level of HMGB1 in serum and Peripheral blood mononuclear cells from SLE patients was higher than those of The healthy control group. Objectives: The aim of this study was to investigate whether HMGB-1 can lead to senescence BM-MSCs from SLE patients and its possible mechanism. Methods: Tewelve female SLE patients and healthy subjects were enrolled in the study. All patients were females, and their age distribution was similar to that of the cases. All BM-MSCs were Isolated by density gradient centrifugation. Western Blotting and immunofluorescence were used to distinguish the difference of expression and localization of TLR4 signaling pathway between normal group and SLE group. Different concentrations (0.01, 0.1, 1, 10ug/ml) of HMGB-1 (the endogenous ligand of TLR4) stimulated normal BM-MSCs, then detecting expression of TLR4 signal by WB, observing the activity of β-gal of cells, the changes of cytoskeletal structure by F-actin staining and the distribution of cell cycle by flow cytometry. We used small interfering RNA (siRNA) to interfere the expression of TLR4. Results: BM-MSCs from SLE patients showed prominent features of senescence, characterized by impaired capacities of proliferation, increased SA-β-gal activity, and disordered cytoskeleton distribution, and abnormal activation of TLR4 signaling transduction, high level of phosphorylated p65. IκBα. After stimulation of HMGB1 in normal MSCs, TLR4 signaling was activated. And, the cell volume and the number of SA-β-gal positive in SLE BM-MSCs was increased. The organization of cytoskeleton was neatly disordered. The rate of cell proliferation was decreased. The inhibitors of HMGB-1 and small interfering RNA (siRNA) of TLR4 can significantly reverse the senescence. Conclusions: HMGB-1 binded to TLR4, and by activating MyD88/IRAK/TRAF pathway, promoted NF-κB signal transduction, thereby affected the expression of cell cycle-related proteins, and then resulted in senescence of MSCs from SLE patients. Acknowledgements: This research was supported by grants from the National Natural Science Foundation of China (81471603). Disclosure of Interest: None declared